Erratum: Disc-jet coupling in the Terzan 5 neutron star X-ray binary EXO 1745-248 [MNRAS 461, 3598 (2016)] - Tetarenko, A.; Bahramian, A.; Sivakoff, G.; Tremou, E.; Linares, M.; Tudor, V.; Miller-Jones, James; Heinke, C.; Chomiuk, L.; Strader, J.; Altamirano, D.; Degenaar, N.; et al. (Oxford University Press, 2016)
The paper "Disc-Jet Coupling in the Terzan 5 Neutron Star X-ray Binary EXO 1745-248" was published as Tetarenko et al. 2016, MNRAS, 460, 345-355. In Section 3.3 of the paper there is a minor error in equation (1). The correct equation is as follows, (logLR - logLR,c) = log ? + ß(logLX - logLX,c). (1) The change comes in the first term on the right hand side, which reads log ξ rather then just ξ alone. Using the original version of the equation, with our best fit parameters, will give an incorrect normalization. This minor error is also found in the conclusion section (Section 5), where we restate equation (1). The mistake in equation (1) was simply a typesetting error in the final version of the manuscript, and the correct expression is used in our MCMC fitting algorithm.